Income dynamics in the United Kingdom and the impact of the Covid‐19 recession. Issue 4 (1st December 2022) - Bell, Brian; Bloom, Nicholas; Blundell, Jack
Abstract : In this paper, we use an employer‐based survey of earnings and hours to set out the key patterns in UK earnings dynamics from 1975 to 2020, with a particular focus on the most recent recession. We demonstrate that (log) earnings changes exhibit strongly procyclical skewness and have become increasingly leptokurtic, and thus less well approximated by a log‐normal distribution, over the period of study. This holds across genders and sectors. Exploiting the long duration of our panel, we then explore the responsiveness of earnings and hours to aggregate and firm‐level shocks, finding ample heterogeneity in the exposure of different types of workers to aggregate shocks. Exposure is falling in age, firm size, skill level, and permanent earnings, and is lower for unionized and public sector workers. The qualitative patterns of earnings changes across workers observed in the Covid‐19 recession of 2020 are broadly as predicted using the previously estimated exposures and size of the shock. Firm‐specific shocks are important for wages given the variation in within‐firm productivity and the patterns of heterogeneity are markedly different than for aggregate shocks.